Single-cell RNA sequencing in silent corticotroph tumors confirms impaired POMC processing and provides new insights into their invasive behavior. Issue 1 (12th May 2022) - Zhang, Dongyun; Hugo, Willy; Bergsneider, Marvin; Wang, Marilene B; Kim, Won; Vinters, Harry V; Heaney, Anthony P
Abstract: Objective: Provide insights into the defective POMC processing and invasive behavior in silent pituitary corticotroph tumors. Design and methods: Single-cell RNAseq was used to compare the cellular makeup and transcriptome of silent and active corticotroph tumors. Results: A series of transcripts related to hormone processing peptidases and genes involved in the structural organization of secretory vesicles were reduced in silent compared to active corticotroph tumors. Most relevant to their invasive behavior, silent corticotroph tumors exhibited several features of epithelial-to-mesenchymal transition, with increased expression of mesenchymal genes along with the loss of transcripts that regulate hormonal biogenesis and secretion. Silent corticotroph tumor vascular smooth muscle cell and pericyte stromal cell populations also exhibited plasticity in their mesenchymal features. Conclusions: Our findings provide novel insights into the mechanisms of impaired POMC processing and invasion in silent corticotroph tumors and suggest that a common transcriptional reprogramming mechanism simultaneously impairs POMC processing and activates tumor invasion.